2018
DOI: 10.1186/s12913-018-3180-0
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities among Asian Americans in inpatient acute myocardial infarction mortality in the United States

Abstract: Background: Acute myocardial infarction (AMI) is a common high-risk disease with inpatient mortality of 5% nationally. But little is known about this outcome among Asian Americans (Asians), a fast growing racial/ethnic minority in the country. The objectives of the study are to obtain near-national estimates of differences in AMI inpatient mortality between minorities (including Asians) and non-Hispanic Whites and identify comorbidities and sociodemographic characteristics associated with these differences. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
(32 reference statements)
2
17
2
Order By: Relevance
“…16,18 Additionally, AA patients are less likely to receive percutaneous coronary intervention, angiography, drug-eluting stents, and coronary artery bypass grafting. 12,18,21,22 Multiple explanations have been postulated; in part, this may be due to misdiagnosis of ACS owing to higher comorbidities or lack of resources resulting in slower referral for procedures, deliberate refusal of angiography interventions, 12 and limitations to access with deterrence from associated costs of seeking care. 18 Moreover, causes for the gaps in procedural rates may extend beyond health care systems and be rooted in personal motivations, including trust level, hesitancies, and preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,18 Additionally, AA patients are less likely to receive percutaneous coronary intervention, angiography, drug-eluting stents, and coronary artery bypass grafting. 12,18,21,22 Multiple explanations have been postulated; in part, this may be due to misdiagnosis of ACS owing to higher comorbidities or lack of resources resulting in slower referral for procedures, deliberate refusal of angiography interventions, 12 and limitations to access with deterrence from associated costs of seeking care. 18 Moreover, causes for the gaps in procedural rates may extend beyond health care systems and be rooted in personal motivations, including trust level, hesitancies, and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…While conflicting evidence continues to be observed, remarkably, some studies have found that despite the dwindling rates of timely procedures, AA patients had lower in-hospital mortality rates compared with other underrepresented groups. 18,22 However, once discharged, AA patients report extensively more adverse symptoms resulting in more clinic visits 1 month after an ACS admission. 12,16 Consequently, repeat hospitalization rates after ACS events are significantly higher in AA patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Both patient-and provider-related barriers can significantly contribute to health and health care disparities, which can in turn influence patients' perceptions of care and negatively affect health outcomes, especially in vulnerable groups. Regarding patient-related barriers, racial and ethnic minority groups have higher inpatient mortality rates from severe acute respiratory failure, 9 acute myocardial infarction, 10 and sepsis than non-Hispanic Whites. 11 Sexual minorities neither see nor receive health care services as often as heterosexual patients because of factors such as perceived discrimination, prejudice, poor provider-patient experiences, lack of culturally competent providers, potential harassment in medical settings, and lack of insurance coverage.…”
Section: Disparities In Health Carementioning
confidence: 99%
“…First, recent studies have shown poor health outcomes among Asians and we hypothesize that this may be associated with low healthcare utilization. 5 Second, continuity of care or frequent ambulatory care utilization is associated with improved healthcare outcomes and lower rates of emergency room visits. Third, the Asian population has been growing faster than the overall national population, which means that their health outcomes will have increasing significance in national healthcare outcomes.…”
Section: Introductionmentioning
confidence: 99%